Looking Like a Million Dollars: Does Attractiveness Priming Increase Altruistic Behavior in Experimental Games? - Novakova, Julie; Machová, Kamila; Sýkorová, Katerina; Zíka, Vojtěch; Flegr, Jaroslav (Frontiers in Psychology, 2021)
The emergence of altruistic behavior constitutes one of the most widely studied problems in evolutionary biology and behavioral science. Multiple explanations have been proposed, most importantly including kin selection, reciprocity and costly signaling in sexual selection. In order to test the latter, this study investigated whether people behave more altruistically when primed by photos of attractive faces, and whether more or less altruistic people differ in the number of sexual and romantic partners. General-population participants (N=158, 84 F, 74 M) first rated the attractiveness of photographs of twenty faces of the opposite (sexually preferred) sex and then played the Dictator and Ultimatum Games. The photograph rating acted as priming; half the participants received photos of people rated as more attractive than average in an earlier study, the other half received photos previously rated as less attractive. The attractiveness-primed participants, especially men, were expected to behave more altruistically – signaling that they are desirable, resources-possessing partners. We also expected altruists to self-report more sexual and romantic partners. The observed difference between altruistic behavior in the attractiveness- and unattractiveness-primed groups occurred in Ultimatum Game offers, however, in the opposite than expected direction in women. The number of sexual partners was positively correlated to minimum acceptable offers in the Ultimatum Game, in line with expectations based on the theory of costly signaling.